2022
DOI: 10.1097/rlu.0000000000004022
|View full text |Cite
|
Sign up to set email alerts
|

Increased 18F-ALF-NOTA-FAPI and 18F-FDG Uptake in Renal Angiomyolipoma

Abstract: Angiomyolipoma is a common benign tumor in the kidney. Previous publication reported that renal angiomyolipoma had very low to low uptake of 18 F-FDG. We report a case of pathologically proven angiomyolipoma in the left kidney with intense 18 F-FDG and 18 F-ALF-NOTA-FAPI uptake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…Currently, fibroblast activating protein (FAP)-specific PET tracers have been reported for imaging various types of renal malignant and benign diseases. [8][9][10][11][12][13][14][15][16] In this case, renal leiomyoma showed intense 68 Ga-FAPI uptake, which may be due to the activation of pathological interstitial tissue causing increased expression of FAP. In this case, low glucose transporter but high FAP may be expressed in the renal leiomyoma; thus, this lesion demonstrated a slight 18 F-FDG but intense 68 Ga-FAPI uptake.…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…Currently, fibroblast activating protein (FAP)-specific PET tracers have been reported for imaging various types of renal malignant and benign diseases. [8][9][10][11][12][13][14][15][16] In this case, renal leiomyoma showed intense 68 Ga-FAPI uptake, which may be due to the activation of pathological interstitial tissue causing increased expression of FAP. In this case, low glucose transporter but high FAP may be expressed in the renal leiomyoma; thus, this lesion demonstrated a slight 18 F-FDG but intense 68 Ga-FAPI uptake.…”
mentioning
confidence: 67%
“…18 F-FDG PET/CT imaging findings for leiomyomas of the nasal, 3 duodenal, 4 rectal, 5 uterine, 6 esophageal, and genital 7 have been reported in some previous literature, and these leiomyomas demonstrated varying degrees of 18 F-FDG uptake. Currently, fibroblast activating protein (FAP)–specific PET tracers have been reported for imaging various types of renal malignant and benign diseases 8–16 . In this case, renal leiomyoma showed intense 68 Ga-FAPI uptake, which may be due to the activation of pathological interstitial tissue causing increased expression of FAP.…”
mentioning
confidence: 87%
“…31 Guo et al showed that angiogenesis correlated positively with 18F-FDG uptake in lung adenocarcinomas. 32 Kaira et al showed that the metabolic activity of primary tumors as evaluated by PET study with 18F-FMT and 18F-FDG was related to tumor angiogenesis and the proliferative activity in non-small cell lung cancer. 33 Studies had also shown that 18F-FDG kinetics were modulated by angiogenesis-related gene.…”
Section: Discussionmentioning
confidence: 99%
“…A few case reports showed intense FAPI uptake in renal angiomyolipomas of the patients without tuberous sclerosis complex. [12][13][14]…”
Section: Figurementioning
confidence: 99%